The role of Corporate Communications in promoting a - Hawabhay, Bharati Bina (My University, 2011)
To sustain long-term survival in today’s business environment, organisations must strive to break from the competitive clutter and become more visible by maintaining a positive image and reputation. This requires a holistic understanding of the communication process from a corporate branding perspective. This research investigated the role of corporate communications in promoting a coherent corporate brand image and reputation in Mauritius. Empirically, this research is based on semi-structured, in-depth interviews with key executives and external stakeholders such as communication consultants, investors and journalists. The findings validated many of the theories proposed in literature and revealed how corporate communications must be integrated and well managed to enable differentiation through the corporate brand. Since expert guidance is necessary, it is advocated that the corporate branding process be coordinated by both the chief executive and the communication director. Additional insights gained from this study have been proposed as a ‘de jure’ model
MBA - WBS
Keywords: Corporate image; Corporate branding; Corporate communications